Missing - Cresswell, Jasmine (Don Mills, Ont. : MIRA, 2007)
When her father disappears with millions of dollars, which exposes his secret double life, Megan Raven, to save her family from further pain, must help bank manager Adam Fairfax search for the missing money and uncovers a tangled web of lies, secrecy, and greed.
Keywords: Bigamy -- Fiction; Missing persons -- Fiction; Suspense fiction; Suspense fiction